1992
DOI: 10.1159/000129210
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Ciclosporin Pretherapyon 90% Hepatectomized Rats

Abstract: We studied the effect of ciclosporin (Cs) on rats which underwent a 90% hepatectomy. Rats were divided into two groups: group 1 (without Cs pretreatment) and group 2 (with Cs pre-treatment). Animals were given a 4-day treatment of Cs (10 mg/kg/day) prior to hepatectomy. The 1-week survival, serum biochemistry and parameters for hepatocyte proliferation (indices for mitosis and 5-bromo-2-deoxyuridine uptake) were serially investigated. Although Cs pretherapy significantly upregulated liver cell proliferation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, other authors didn't achieve the same results 12,13 . In this study, the authors used oral cyclosporine in a 10mg/Kg/day with rigid plastic orogastric tube as described by other researchers [9][10][11][15][16][17][18] . All groups lost body weight in the moment of death with statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…However, other authors didn't achieve the same results 12,13 . In this study, the authors used oral cyclosporine in a 10mg/Kg/day with rigid plastic orogastric tube as described by other researchers [9][10][11][15][16][17][18] . All groups lost body weight in the moment of death with statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Pre treatment with testosterone improved the sur vival after a 90% hepatectomy, with a reduc tion of the steatosis observed in the liver [11], The hypoglycemia occurring after a 90% he patectomy can be prevented by adding glu cose to the drinking water and this simple measure improves the survival rate [13], The administration of cyclosporine or of OK-432, an immunostimulant of streptococcal origin that increases the reticuloendothelial system activity, enhanced liver regeneration and in creased the survival rate [18,19], Hepatocyte or microcarrier-attached hepatocyte trans plantation reduces the acute hepatic failure induced by a 90% hepatectomy in the rat [ 17,20,21] In addition to these various treatments giv en after or at the time of partial hepatectomy, attempts have been made to modify the liver before the anticipated resection. As it was observed that the mitochondrial function and mitochondrial mRNA are elevated in the nonligated lobes during the first 48 h after a PBL.…”
Section: Discussionmentioning
confidence: 99%